The Contribution of Basic Leadership Training (LDK) to the Soft Skill Competency of Students of Special School (SLB) Bina Harapan - Zuli Dwi Rahmawati; Bisarul Ihsan (EDUTEC : Journal of Education And Technology, 2022)
The purpose of this study was to describe the real contribution of changes in the soft skill competence of students with special needs (deaf speech) at the Bina Harapan Special School as a result of basic leadership training. This research is included in qualitative descriptive research with a case study approach. The results of this study are 1) Students' communication competence is good, this is evidenced by the many conversations that occur in one day, both with fellow speech-impaired students and with other people who do not have special needs. 2) The competence of being able to cooperate with students is very good, as evidenced by their getting used to doing activities with other friends and supported by the habituation of group work by the school. 3) The adaptability of students is very good, as evidenced by the ratio of the number of close friends they mention is currently much higher than when they first entered school. 4) The leadership competence of students is very good, as evidenced by the way they lead themselves to be able to move others in addition to learning activities, homework and their circumstances. 5) Students' problem solving competence is well proven by the way they deal with problems that come from themselves and from others.